Analisis Sistem Informasi Akuntansi Penerimaan dan Pengeluaran Kas Pengelolaan Zakat di Badan Amil Zakat Nasional (BAZNAS) Kabupaten Labuhanbatu - Aulia Rahmah Pasaribu; Fauzi Arif Lubis; Arnida Wahyuni Lubis (Jurnal Riset Ekonomi dan Akuntansi, 2023)
Research on accounting information systems is important to carry out because of inaccurate data and transaction evidence as well as a lack of human resources as reporting actors so that the reports presented are less accurate and not realized perfectly. This research aims to determine the application of the Cash Receipt and Distribution Accounting Information System in Zakat Management at BAZNAS Labuhanbatu Regency. This research uses a qualitative research method with a qualitative descriptive approach and the data collection techniques used are observation, interviews and obtaining data and information in the form of financial report documents. The results of this study indicate that BAZNAS Labuhanbatu Regency. The data obtained are primary and secondary data, while primary data is obtained from statements from the chairman and staff of BAZNAS, while secondary data is reports on the receipt and distribution of Zakat, Infaq and alms funds. The research results show that BAZNAS Labuhanbatu Regency already has a report on the receipt and distribution of zakat funds based on PSAK 109, however the report is still said to be incomplete due to the lack of human resources at BAZNAS Labuhanbatu Regency